Rodinný dům s provozovnou - Grepl, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2017)
TÉMA BAKALÁŘSKÉ PRÁCE JE RODINNÝ DŮM S PROVOZOVNOU V KROMĚŘÍŽI. STAVBA MÁ DVĚ NADZEMNÍ PODLAŽÍ A ČÁSTEČNÉ PODSKLEPENÍ. DŮM MÁ BYTOVOU ČÁST PRO PĚT OSOB A PROVOZOVNU PRO DVĚ OSOBY. OBJEKT MÁ NOSNÝ SYSTÉM Z POROTHERMU. BYLA ZVOLENA KOMBINACE PLOCHÉ STŘECHY NAD PROVOZOVNOU A SEDLOVOU STŘECHOU NAD OBYTNOU ČÁSTÍ. ZÁKLADY TVOŘÍ ZÁKLADOVÉ PÁSY.

THE BACHELOR'S WORK IS A FAMILY HOUSE IN THE TOWN KROMERIZ WORKING OPERATOR. BUILDING HAS TWO FLOOR FLOOR AND PARTIAL GROUNDING. HOUSE HAS AN APARTMENT FOR FIVE PERSONS AND A TWO PERSONNEL OPERATOR. THE OBJECT HAS A POROTHERM SYSTEM. COMBINATION OF FLOOR ROOFS BEYOND THE OPERATING AND SADDLE ROOF BEYOND THE CIVIL PARTS. BASES FOUND BASIC BELTS.
Family house with an establishment
Keywords: RODINNÝ DŮM S PROVOZOVNOU; POROTHERM; KOMBINACE STŘECH; FAMILY HOUSE WITH OPERATING; POROTHERM; ROOF COMBINATION